Do negacionismo da extrema direita brasileira em discursos sobre a ditadura militar no brasil (1964-1985) à constituição de uma proposta arquegenealógica para o ensino de história - Alves, Alison Sullivan de Sousa (2021)
The present work problematizes the historical denialism identified in political discourses of the Brazilian extreme right about the Military Dictatorship of Brazil and seeks to constitute a didactic proposal related to the theme for the teaching and learning of History in basic education, through Foucault's archegenealogy. Therefore, it brings as an object / problem the questioning about the pedagogical possibilities for research and discourse analysis in the classroom, specifically, around the aforementioned knowledge object, based on the Foucaultian archegenealogical method. Its general objective is to analyze the negative speech of the Brazilian extreme right about the Military Dictatorship of Brazil and the possibility of constituting a methodological proposal for teaching and learning archegenealogical of History around that school theme. It is a descriptive-qualitative study, whose approach follows a predominantly qualitative bias and brings as a methodology the discourse analysis, under the guidance of Foucault's archegenealogy, to think and build a didactic proposal that values the teacher-student dialogue, the contextualization of learning and interdisciplinarity, and make meaningful research in the classroom an effective and active way to study history. Our corpus is constituted of 42 discursive materialities related to the problem of this work, on which the analysis proposes to identify the discursive regularities and to problematize the “wills of truth” found, envisioning them in a didactic situation. The main authors that make up the theoretical foundation are: Foucault and the works Arqueologia do saber (2008) and Microfísica do poder (1998), to study the fundamental notions about discourse analysis and conceptualize the archegenealogical method; Dreifuss (1981) for the historiographical study of the seizure of power and the authoritarian regime inaugurated in Brazil in 1964; to assist in the constitution of a didactic-pedagogical proposal on the subject in question, we brought the dialogic method of Freire and Shor (1986), the methodology of the contextualization of Atina's learning, presented by Andrade and Sartori (2016) and the basic concepts of History, reverberated by Bittencourt (2008). And Courtine (2009) for the theoretical orientation of constituting a discursive corpus. The research presents as main results the finding of a negationist discourse that generates inflections in society about the Military Dictatorship of Brazil and, in this sense, presents itself as a challenge for the current Brazilian historiography, but, also, that can be problematized in the classroom. History class, using active resources and methodologies, mediated by authors like Foucault who reflect on discourse as a political and social practice